New Hypervariable SSR Markers for Diversity Analysis, Hybrid Purity Testing and Trait Mapping in Pigeonpea [Cajanus cajan (L.) Millspaugh] - Bohra, Abhishek; Jha, Rintu; Pandey, Gaurav; Patil, Prakash G.; Saxena, Rachit K.; Singh, Indra P.; Singh, D.; Mishra, R. K.; Mishra, Ankita; Singh, F.; Varshney, Rajeev K.; Singh, N. P. (Frontiers in Plant Science, 2017)
Draft genome sequence in pigeonpea offers unprecedented opportunities for genomics assisted crop improvement via enabling access to genome-wide genetic markers. In the present study, 421 hypervariable simple sequence repeat (SSR) markers from the pigeonpea genome were screened on a panel of eight pigeonpea genotypes yielding marker validation and polymorphism percentages of 95.24% and 54.11%, respectively. The SSR marker assay uncovered a total of 570 alleles with three as an average number of alleles per marker. Similarly, the mean values for gene diversity and PIC were 0.44 and 0.37, respectively. The number of polymorphic markers ranged from 39-89 for different parental combinations. Further, 60 of these SSRs were assayed on 94 genotypes, and model based clustering using STRUCTURE resulted in the identification of the two subpopulations (K=2). This remained in close agreement with the clustering patterns inferred from genetic distance (GD)-based approaches i.e. dendrogram, factorial and principal coordinate analysis (PCoA). The AMOVA accounted majority of the genetic variation within groups (89%) in comparison to the variation existing between the groups (11%). A subset of these markers was implicated for hybrid purity testing. We also demonstrated utility of these SSR markers in trait mapping through association and bi-parental linkage analyses. The general linear (GLM) and mixed linear (MLM) models both detected a single SSR marker (CcGM03681) with R2=16.4 as associated with the resistance to Fusarium wilt variant 2. Similarly, by using SSR data in a segregating backcross population, the corresponding restorer-of-fertility (Rf) locus was mapped at 39 cM with the marker CcGM08896. However, the MTAs detected here represent a very preliminary type and hence demand deeper investigations for conclusive evidence. Given their ability to reveal polymorphism in simple agarose gels, the hypervariable SSRs are valuable genomic resource for pigeonpea research community, particularly in South Asia and East Africa where pigeonpea is primarily grown.